Cytotoxic T Lymphocytes in Rasmussen's Encephalitis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
The role of cytotoxic T lymphocytes and other mechanisms in the pathogenesis of Rasmussen's encephalitis (RE) is reviewed at the University of Vienna, Austria, and the University of Bonn, Germany.